Solve the equation x 3 − 1 2 x 2 + 4 8 x − 6 4 = 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The main thing is how did you know that it has to be split in this way only because there are millions of ways
why u split -12 to -4-8 and 48 to 32+16, I'm confused
Apply the substitution x = y − 3 a b = y − 3 ( 1 ) − 1 2 = y + 4 and simplify to get y 3 = 0 which has 0 as a root with multiplicity 3.So one root of the equation is x = y + 4 = 0 + 4 = 4 meaning x − 4 is a factor.Upon dividing we get x 2 − 8 x + 1 6 which can be factored as ( x − 4 ) 2 so the cubic can be factored as ( x − 4 ) 3 = 0 therefore the equation has one real root with multiplicity 3 which is 4
In this question three root will be possible so we can do in this way
P, Qand Rbe the three root so 64 is multiple of 4×4× 4.and 12be the sum of 4+4+4 so we can say that the valu ofX be 4i.eX=4
Problem Loading...
Note Loading...
Set Loading...
Solution in detail
x 3 − 1 2 x 2 + 4 8 x − 6 4 = 0
We know that − 1 2 x 2 = − 4 x 2 − 8 x 2 and 4 8 x = 3 2 x + 1 6 x , substitute inside the equation we will get
x 3 − 4 x 2 − 8 x 2 + 3 2 x + 1 6 x − 6 4 = 0
divide this equation into 3 parts which is
( x 3 − 4 x 2 ) + ( − 8 x 2 + 3 2 x ) + ( 1 6 x − 6 4 ) = 0
Factor 1 part by 1 part
We will get x 2 ( x − 4 ) − 8 x ( x − 4 ) + 1 6 ( x − 4 ) = 0
Factor out x − 4
( x 2 − 8 x + 1 6 ) ( x − 4 ) = 0
Factor the quadratic equation in front
x 2 − 2 ( 4 ) x + 4 2 , we know that ( a − b ) 2 = a 2 + b 2 − 2 a b
So, ( x − 4 ) ( x − 4 ) ( x − 4 ) = 0 which is ( x − 4 ) 3 = 0
The only root is x = 4
Share your solution if you solved this too :)